Synthesis of the C14-C29 segment of amphidinolide U utilizing a tandem dihydroxylation-S(N)2 cyclization protocol - Mohapatra, Debendra K.; Rahaman, Hasibur (Synlett, 2008)
The synthesis of the C14-C29 subunit of amphidinolide U is described. The key steps include the trans-2,5-disubstituted tetrahydrofurans via a highly diastereoselective and high yielding tandem dihydroxylation-S(N)2 cyclization, Wittig reaction, and Nozaki-Hiyama-Kishi coupling reaction.
Keywords: amphidinolide U; Cytotoxic; Nozaki-Hiyama-Kishi coupling; tandem dihydroxylation-S(N)2 cyclization; Wittig reaction